Three-dimensional high-resolution crystallographic observation of the entire volume of microstructurally small fatigue cracks in Ni-Co based superalloy. (1st January 2023) - Nishikawa, Hideaki; Furuya, Yoshiyuki; Osada, Toshio; Kawagishi, Kyoko; Hara, Toru
Abstract: The crystallographic features of microstructurally small fatigue cracks (MSFCs) in a Ni-Co-based superalloy were analyzed by using a Xe plasma focused ion beam scanning electron microscope (PFIB-SEM) system in conjunction with electron backscatter diffraction (EBSD) analysis. The crystallographic orientation of the three-dimensional (3D) fatigue crack growth path was successfully observed using a large-volume, high-resolution 3D image. The major parts of the crack surface were close to the 111 slip plane. Our results indicated that the Mode II fatigue crack growth mechanism is locally more predominant than the general blunting-resharpening Mode I fatigue crack growth mechanism, not only in the Stage I region but also in the larger part of the Stage II region of MSFC growth process. Graphical abstract: Image, graphical abstract